Preparation method of silver-coated copper powder
Through the one-pot method, the two-step step-by-step silver-covered copper powder preparation method is solved, and the existing silver-covered copper powder preparation method and uneven coating effect are prepared, and dense and stable silver-covered copper powder is improved, which improves the conductivity and particle uniformity.
Patent Information
- Application Number
- CN202411749916.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
The existing silver-clad copper powder preparation method is complex, and the coating effect is uneven, resulting in poor conductivity and high cost.
The method of covering silver with two steps in one-pot method is adopted. First, the silver shell is quickly coated with a high-concentration silver ammonia solution, and then gradually tighten the dense coating with a low-concentration silver ammonia solution.
The silver-clad copper powder with dense appearance and stable structure was prepared, which reduced the silver content, while improving the conductivity and particle uniformity, and reducing agglomeration.
Smart Images

Figure CN119549705A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials and relates to a method for preparing silver-coated copper powder. Background Art
[0002] In recent years, the rapid rise of flexible electronic devices has led to an increasing demand for functional conductive pastes, which need to have excellent electrical, thermal, construction and mechanical properties. The main conductive particles of existing conductive pastes are silver powders of different specifications. Silver powders have low resistivity and relatively stable chemical properties, but silver migrates and is expensive, which greatly increases the cost of conductive pastes and severely restricts the development of the industry. Therefore, using low-cost silver-coated copper powder to replace silver powder as conductive particles will become a trend.
[0003] Silver-coated copper powder is a copper powder with a layer of silver shell on its surface, which solves the problem of copper oxidation and silver migration. More importantly, it has a greater cost advantage compared to silver powder. However, due to the harsh application environment of conductive paste, silver-coated copper powder needs to have a low silver content while ensuring sufficient corrosion resistance, which requires the silver-coated copper powder to have high density. Therefore, it is urgent to prepare silver-coated copper powder with high density and low silver content.
[0004] Chinese patent CN111304640A discloses a method for preparing silver-coated copper powder, wherein the copper powder is first coated with a first silver-ammonia solution, and then coated with a second silver-ammonia solution after separation, thereby obtaining the silver-coated copper powder. However, this technology has the following disadvantages: (1) the silver coating is carried out in two steps, which may result in low bonding strength between the two layers of coated silver; (2) the preparation method is relatively complicated, and the two silver coatings and intermediate treatments increase the number of operation steps and the process cycle; (3) the obtained silver-coated copper powder has obvious agglomeration or uneven coating.
[0005] Therefore, it is necessary to continue to improve the preparation method of silver-coated copper powder, so that the preparation method is simpler and the coating effect is better and more uniform. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing silver-coated copper powder.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing silver-coated copper powder comprises the following steps:
[0009] The first silver ammonia solution and the first reducing agent solution are simultaneously added dropwise to the deoiled and activated spherical copper powder dispersion, reacted for 5-20 minutes after the addition is completed, and then the second silver ammonia solution and the second reducing agent solution are simultaneously added dropwise, reacted for 25-40 minutes, filtered, washed with water, and dried to obtain the silver-coated copper powder;
[0010] The concentration of the first silver ammonia solution is 0.3-2 mol / L;
[0011] The concentration of the second silver ammonia solution is 0.005-0.1 mol / L.
[0012] Preferably, the activation solution used for the activation is selected from one of sulfuric acid solution, phosphoric acid solution, hydrochloric acid solution, benzenesulfonic acid solution, trifluoromethylbenzenesulfonic acid solution, C1-C4 alkylsulfonic acid solution and aminosulfonic acid solution.
[0013] Preferably, the average particle size of the spherical copper powder is 0.5-20 μm.
[0014] Preferably, the first reducing agent and the second reducing agent are independently selected from one or a combination of two or more of hydrazine hydrate, dimethylhydrazine, sodium borohydride, glucose, ascorbic acid and its salts and tartaric acid and its salts.
[0015] Preferably, the molar ratio of the first silver ammonia in the first silver ammonia solution to the first reducing agent in the first reducing agent solution is 1:1-5.
[0016] Preferably, the molar ratio of the second silver ammonia in the second silver ammonia solution to the second reducing agent in the second reducing agent solution is 1:1-10.
[0017] Preferably, the molar concentration of the first silver ammonia solution is 20 times or more than the molar concentration of the second silver ammonia solution.
[0018] Preferably, the molar number of silver ammonia in the first silver ammonia solution is 30 times or more than the molar number of silver ammonia in the second silver ammonia solution.
[0019] Preferably, the end point of the water washing is when the conductivity of the washing liquid is less than 15 μs / cm.
[0020] A silver-coated copper powder is prepared by the preparation method of the silver-coated copper powder described in any one of the above technical solutions.
[0021] The beneficial effects of the present invention are:
[0022] (1) The present invention adopts a "one-pot method" through a two-step step-by-step silver coating method, using different concentrations of silver ammonia solutions to control the silver reduction and deposition rate, first using a high concentration of silver ammonia solution to quickly coat the silver on the surface of the copper powder into a shell, and then using a low concentration of silver ammonia solution to gradually compact the silver shell, thereby preparing a silver-coated copper powder with a dense appearance and stable structure.
[0023] (2) The silver content in the silver-coated copper powder obtained by the present invention can be relatively low, for example, the silver content in the silver-coated copper powder can be 10-20wt%, and no additional dispersant, ammonia water and other substances are required. The silver-coated copper powder has relatively regular and uniform particles, and less agglomeration phenomenon, which is more conducive to improving the conductive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the SEM image of the silver-coated copper powder obtained in Example 1.
[0025] Figure 2 This is the SEM image of the silver-coated copper powder obtained in Example 1.
[0026] Figure 3 This is the SEM image of the silver-coated copper powder obtained in Comparative Example 1. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0028] The coating effect of the silver coating layer has an impact on the conductivity of the silver-coated copper powder. Generally, the denser, more uniform and less agglomerated the silver coating layer is, the better the conductivity of the silver-coated copper powder is. Therefore, in order to improve the coating effect of the silver-coated copper, the present invention provides a method for preparing the silver-coated copper powder, comprising the following steps:
[0029] The first silver ammonia solution and the first reducing agent solution are simultaneously added dropwise to the deoiled and activated spherical copper powder dispersion, reacted for 5-20 minutes after the addition is completed, and then the second silver ammonia solution and the second reducing agent solution are simultaneously added dropwise, reacted for 25-40 minutes, filtered, washed with water, and dried to obtain silver-coated copper powder;
[0030] The concentration of the first silver ammonia solution is 0.3-2 mol / L;
[0031] The concentration of the second silver ammonia solution is 0.005-0.1 mol / L.
[0032] The present invention adopts a "one-pot method" and a two-step step-by-step silver coating method to prepare silver-coated copper powder. After the copper powder is degreased and activated, a first silver-ammonia solution with a relatively high concentration is firstly used to reduce and quickly coat the surface of the copper powder to form a shell under the action of a first reducing agent, and then a second silver-ammonia solution with a relatively low concentration is directly added to reduce to silver under the action of a second reducing agent and continues to deposit and coat the surface of the copper powder relatively slowly and densely, which not only supplements and densifies the silver coating layer reduced to a shell by the first silver-ammonia solution, but also continues to form a dense and uniform silver coating layer at the same time. Moreover, the preparation method of the present invention has very good dispersibility and uniformity of the silver-coated copper powder obtained, and basically no agglomeration.
[0033] In the present invention, the concentration of the first silver ammonia solution is not particularly limited, and can be any value in 0.3mol / L, 0.5mol / L, 0.7mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.3mol / L, 1.5mol / L, 1.7mol / L, 1.8mol / L, 2mol / L, etc., without particular restrictions. Further, the concentration of the first silver ammonia solution can be 0.3-1.5mol / L. The concentration of the second silver ammonia solution is also not particularly limited, and can be any value in 0.005mol / L, 0.01mol / L, 0.02mol / L, 0.03mol / L, 0.04mol / L, 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.1mol / L, etc., without particular restrictions. Furthermore, the concentration of the second silver ammonia solution can be 0.005-0.08 mol / L, and further, the concentration of the second silver ammonia solution can be 0.005-0.05 mol / L. In the present invention, the weight ratio of the copper powder to the silver ammonia in the first silver ammonia solution is not particularly limited, and can be 100:10-18. For example, the weight ratio can be any value of 100:10, 100:11, 100:12, 100:13, 100:14, 100:15, 100:16, 100:17, 100:18, etc., without particular limitation.
[0034] The surface of the copper powder may contain an oxide film layer and pollutants such as grease. The copper powder can be degreased with degreasing agents such as organic solvents, acids, alkalis or surfactants. For example, the degreasing agent can be acetone, 0.5-10wt% sulfuric acid solution, emulsifier OP-10, surfactant K12, surfactant AEO-9, surfactant AEO-12 and 0.5-10wt% sodium hydroxide solution, or a combination of two or more degreasing agents, such as a combination of sulfuric acid solution and surfactant, a combination of sodium hydroxide solution and surfactant, etc. After the surface of the copper powder is degreased, it is immersed in an activation solution for activation, which can not only remove the oxide layer on the surface, but also activate the copper powder to improve the binding force of the copper powder to the reduced silver coating layer. The degreasing treatment and activation treatment can also be completed in one step. For example, the surface treatment of the copper powder by a combination of sulfuric acid solution and surfactant can complete the degreasing and activation at one time. After the copper powder is degreased and activated, it can be washed to neutrality with ultrapure water or deionized water. In a preferred embodiment of the present invention, the activation solution used for activation can be selected from a strong acid solution, and the concentration can be 0.5-10wt%, such as one of sulfuric acid solution, phosphoric acid solution, hydrochloric acid solution, benzenesulfonic acid solution, trifluoromethylbenzenesulfonic acid solution, C1-C4 alkylsulfonic acid solution and aminosulfonic acid solution. The activation temperature can be 10-80°C, and the activation time can be 1-10h. In order to improve the activation efficiency, stirring or ventilation bubbling method can be adopted.
[0035] In a preferred embodiment of the present invention, the average particle size of the spherical copper powder is 0.5-20 μm, which can be directly obtained from the market. For example, the average particle size of the spherical copper powder can be any value of 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, etc., without special restrictions. The dispersion of the spherical copper powder can be an aqueous dispersion of the spherical copper powder, and the concentration can be 1-10 wt%.
[0036] In a preferred embodiment of the present invention, the first reducing agent and the second reducing agent are independently selected from one or a combination of two or more of hydrazine hydrate, dimethylhydrazine, sodium borohydride, glucose, ascorbic acid and its salts and tartaric acid and its salts. The silver ammonia solution is easily reduced to silver particles under the action of the reducing agent and gradually deposited on the surface of the copper powder. Ascorbic acid and its salts can be ascorbic acid or sodium ascorbate, and tartaric acid and its salts can be tartaric acid, sodium tartrate, potassium tartrate, potassium sodium tartrate. The concentration of the first reducing agent solution can be 0.8-2mol / L, such as 0.8mol / L, 1mol / L, 1.2mol / L, 1.4mol / L, 1.6mol / L, 1.8mol / L, 2mol / L, etc., and the concentration of the second reducing agent solution can be 0.1-0.5mol / L, such as 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, etc. In the present invention, there is no particular limitation on the reduction reaction temperature of the first silver ammonia solution and the reduction reaction temperature of the second silver ammonia solution. For example, it can be 10-70°C. For example, the reduction reaction temperature of the first silver ammonia solution can be 20°C, 25°C, 30°C, etc., and the reduction reaction temperature of the second silver ammonia solution can be 40°C, 50°C, 60°C, 70°C, etc.
[0037] In order to ensure that silver ammonia can be reduced to silver more quickly and more completely, the reducing agent needs to be sufficient or excessive relative to the silver ammonia. In a preferred embodiment of the present invention, the molar ratio of the first silver ammonia in the first silver ammonia solution to the first reducing agent in the first reducing agent solution is 1:1-5. For example, the molar ratio can be any value of 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc., without special restrictions.
[0038] In a preferred embodiment of the present invention, the molar ratio of the second silver ammonia in the second silver ammonia solution to the second reducing agent in the second reducing agent solution is 1:1-10. For example, the molar ratio can be any value of 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., without any particular limitation.
[0039] In a preferred embodiment of the present invention, the molar concentration of the first silver ammonia solution is 20 times or more than the molar concentration of the second silver ammonia solution. The present invention finds that the molar concentrations of the first silver ammonia solution and the second silver ammonia solution differ greatly, and can form silver reduction and deposition rates that differ greatly before and after, which is more conducive to forming a dense and uniform silver coating. For example, the molar concentration of the first silver ammonia solution can be 20 times, 22 times, 24 times, 25 times, 27 times, 28 times, 30 times, 33 times, 35 times, 37 times, 38 times, 40 times, 42 times, 45 times, 47 times, 48 times, 50 times, etc., of the molar concentration of the second silver ammonia solution, without special restrictions.
[0040] In a preferred embodiment of the present invention, the molar number of silver ammonia in the first silver ammonia solution is 30 times or more than the molar number of silver ammonia in the second silver ammonia solution. The molar number of silver ammonia in the first silver ammonia solution and the molar number of silver ammonia in the second silver ammonia solution are quite different. The weight of the silver coating layer mainly comes from the reduction and deposition of the first silver ammonia solution. The obtained silver coating layer has a faster formation rate, and the second silver ammonia solution is slowly reduced and deposited to compensate for the compactness of the first silver coating layer, thereby improving the compactness of the overall silver coating layer. In the present invention, the silver content in the silver-coated copper powder can be 10-20wt%. For example, the molar number of silver ammonia in the first silver ammonia solution is 30 times, 32 times, 35 times, 37 times, 38 times, 40 times, 42 times, 43 times, 45 times, 47 times, 48 times, 50 times, 52 times, 55 times, 57 times, 58 times, 60 times, 62 times, 63 times, 65 times, 67 times, 68 times, 70 times, etc., of the molar number of silver ammonia in the second silver ammonia solution, without any particular limitation.
[0041] In a preferred embodiment of the present invention, the end point of water washing is when the conductivity of the water washing liquid is less than 15 μs / cm. The degree of removal of impurities on the surface of the silver-coated copper powder can be determined by testing the conductivity of the water washing liquid after washing. When the conductivity of the water washing liquid is less than 15 μs / cm, the silver-coated copper powder can be considered to have been cleaned.
[0042] Another aspect of the present invention provides a silver-coated copper powder, which is prepared by the method for preparing the silver-coated copper powder described in any of the above technical solutions. The silver-coated copper powder of the present invention has a relatively regular structure, a relatively uniform size, and is substantially free of agglomeration, and a volume resistivity of up to 10 -6 Ω·cm level, and the antioxidant performance is also good.
[0043] The technical solution of the present invention is further described and illustrated below based on various embodiments and comparative examples.
[0044] Example 1
[0045] 10 g of spherical copper powder with an average particle size of 3 μm was weighed and placed in 100 mL of a treatment solution containing 5 wt % sulfuric acid and 2 wt % OP-10, degreased and activated at 50° C. for 1 h, and then washed with deionized water until neutral.
[0046] The activated copper powder was added to 200 mL of deionized water for ultrasonic dispersion, and 33 mL of 0.5 mol / L silver ammonia solution and 20 mL of a mixed solution containing 0.4 mol / L glucose and 0.8 mol / L potassium sodium tartrate were added at 20 ° C. The mixture was dripped within 20 min. After the dripping, the mixture was stirred and reacted for 10 min. The mixture was heated to 50 ° C. At the same time, 15 mL of 0.01 mol / L silver ammonia solution and 5 mL of 0.3 mol / L potassium sodium tartrate solution were added. The mixture was dripped within 20 min. The reaction was continued at a constant temperature for 30 min. The reaction solution was filtered, the solid particles were collected and washed with deionized water until the conductivity of the washing liquid was <15 μs / cm, and then vacuum dried at 80 ° C for 6 h to obtain silver-coated copper powder.
[0047] The silver content of the silver-coated copper powder of this embodiment was measured to be 15.2 wt %. The SEM image of the silver-coated copper powder of this embodiment is shown in the attached figure. Figure 1 and attached Figure 2 As shown, it can be seen that the obtained silver-coated copper powder has good particle regularity, good particle size uniformity, and basically no agglomeration.
[0048] Example 2
[0049] The difference between this embodiment and embodiment 1 is that in embodiment 1, 15 mL of 0.01 mol / L silver ammonia solution is adjusted to 15 mL of 0.02 mol / L silver ammonia solution. The remaining steps remain unchanged.
[0050] The silver content of the silver-coated copper powder of this embodiment is measured to be 15.4 wt %. The SEM results of the silver-coated copper powder of this embodiment show that the particles are very regular, the particle size is very uniform, and there is basically no agglomeration.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that in embodiment 1, 15 mL of 0.01 mol / L silver ammonia solution is adjusted to 15 mL of 0.05 mol / L silver ammonia solution. The remaining steps remain unchanged.
[0053] The silver content of the silver-coated copper powder of this embodiment is measured to be 15.7 wt %. The SEM results of the silver-coated copper powder of this embodiment show that the particles have good regularity, good uniformity of particle size, and are basically free of agglomeration.
[0054] Comparative Example 1
[0055] 10 g of the spherical copper powder in Example 1 was degreased and activated according to the method of Example 1.
[0056] The activated copper powder was added to 200 mL of deionized water for ultrasonic dispersion, and the temperature was raised to 50°C. 33.3 mL of 0.5 mol / L silver ammonia solution and 25 mL of a mixed solution containing 0.4 mol / L glucose and 0.8 mol / L potassium sodium tartrate were added dropwise at the same time. The mixture was added dropwise within 25 min, and the mixture was stirred and reacted at a constant temperature for 30 min. The reaction solution was filtered, and the solid particles were collected and washed with deionized water until the conductivity of the washing liquid was <15 μs / cm. The mixture was vacuum dried at 80°C for 6 h to obtain silver-coated copper powder.
[0057] The silver content of the silver-coated copper powder of this comparative example was measured to be 14.7 wt %. The SEM image of the silver-coated copper powder of this comparative example is shown in the attached figure. Figure 3 As shown, it can be seen that the surface silver coating is very uneven and the particles have poor regularity.
[0058] Comparative Example 2
[0059] The difference between this comparative example and comparative example 1 is that in comparative example 1, the temperature is raised to 50° C. and adjusted to room temperature 20° C. The other steps remain unchanged.
[0060] The silver content of the silver-coated copper powder of this comparative example was measured to be 14.5 wt %. The SEM results of the silver-coated copper powder of this comparative example showed that the surface silver coating layer was very uneven and the particle regularity was poor.
[0061] Comparative Example 3
[0062] The difference between this comparative example and Example 1 is that in Example 1, 15 mL of 0.01 mol / L silver ammonia solution is adjusted to 15 mL of 0.12 mol / L silver ammonia solution, and 5 mL of 0.3 mol / L potassium sodium tartrate solution is adjusted to 15 mL of 0.3 mol / L potassium sodium tartrate solution. The remaining steps remain unchanged.
[0063] The silver content of the silver-coated copper powder of this comparative example was measured to be 16.1 wt %. The SEM results of the silver-coated copper powder of this comparative example showed that the surface silver coating layer was very uneven and the particle regularity was poor.
[0064] Example 4
[0065] 10 g of spherical copper powder with an average particle size of 3 μm was weighed and placed in 100 mL of a treatment solution containing 5 wt % sulfuric acid and 2 wt % OP-10, degreased and activated at 40° C. for 2 h, and then washed with deionized water until neutral.
[0066] The activated copper powder was added to 200 mL of deionized water for ultrasonic dispersion, and 46 mL of 0.5 mol / L silver ammonia solution and 28 mL of a mixed solution containing 0.4 mol / L glucose and 0.8 mol / L potassium sodium tartrate were added at 20 ° C. The mixture was dripped within 30 min, and the mixture was stirred and reacted for 10 min after the dripping. The mixture was heated to 45 ° C. At the same time, 21 mL of 0.01 mol / L silver ammonia solution and 7 mL of 0.3 mol / L potassium sodium tartrate solution were dripped, and the mixture was dripped within 30 min. The reaction was continued at a constant temperature for 30 min. The reaction solution was filtered, and the solid particles were collected and washed with deionized water until the conductivity of the washing liquid was <15 μs / cm, and then vacuum dried at 80 ° C for 6 h to obtain silver-coated copper powder.
[0067] The silver content of the silver-coated copper powder of this embodiment is measured to be 19.5 wt %. The SEM results of the silver-coated copper powder of this embodiment show that the particles are very regular, the particle size is very uniform, and there is basically no agglomeration.
[0068] Example 5
[0069] 10 g of spherical copper powder with an average particle size of 3 μm was weighed and placed in 100 mL of a treatment solution containing 5 wt % sulfuric acid and 2 wt % OP-10, degreased and activated at 60° C. for 1 h, and then washed with deionized water until neutral.
[0070] The activated copper powder was added to 200 mL of deionized water for ultrasonic dispersion, and 23 mL of 1.0 mol / L silver ammonia solution and 28 mL of a mixed solution containing 0.2 mol / L ascorbic acid and 1.0 mol / L sodium tartrate were added at 20 ° C. The mixture was dripped within 15 min. After the dripping, the mixture was stirred and reacted for 10 min. The mixture was heated to 70 ° C. At the same time, 15 mL of 0.04 mol / L silver ammonia solution and 7 mL of 0.3 mol / L sodium tartrate solution were dripped. The mixture was dripped within 30 min. The reaction was continued at a constant temperature for 30 min. The reaction solution was filtered, the solid particles were collected and washed with deionized water until the conductivity of the washing liquid was <15 μs / cm, and then vacuum dried at 80 ° C for 6 h to obtain silver-coated copper powder.
[0071] The silver content of the silver-coated copper powder of this embodiment is measured to be 19.3 wt %. The SEM results of the silver-coated copper powder of this embodiment show that the particles are well-regular, the particle size is well-uniform, and there is basically no agglomeration.
[0072] Example 6
[0073] The difference between this embodiment and embodiment 5 is that in embodiment 5, 23 mL of 1.0 mol / L silver ammonia solution is adjusted to 76 mL of 0.3 mol / L silver ammonia solution. The remaining steps remain unchanged.
[0074] The silver content of the silver-coated copper powder of this embodiment is measured to be 19.4 wt %. The SEM results of the silver-coated copper powder of this embodiment show that the particles have good regularity and uniformity of particle size, and there is basically no agglomeration.
[0075] Example 7
[0076] The difference between this embodiment and embodiment 6 is that in embodiment 6, 15 mL of 0.04 mol / L silver ammonia solution is adjusted to 75 mL of 0.008 mol / L silver ammonia solution. The remaining steps remain unchanged.
[0077] The silver content of the silver-coated copper powder of this embodiment is measured to be 19.2 wt %. The SEM results of the silver-coated copper powder of this embodiment show that the particles are very regular, the particle size is very uniform, and there is basically no agglomeration.
[0078] The silver-coated copper powders prepared in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests. The performance test results are shown in Table 1, and the performance tests include laser particle size (D50), volume resistivity, tap density, and oxidation resistance.
[0079] The antioxidant test method is: take 20 mg of sample and keep it in air atmosphere at 200°C for 2 hours using a thermogravimetric analyzer to detect the weight increase. The greater the weight increase, the worse the antioxidant property.
[0080] Table 1
[0081]
[0082]
[0083] Therefore, according to the experimental results of the above embodiments and comparative examples, the silver-coated copper powder obtained by the preparation method of the silver-coated copper powder of the present invention has good particle regularity, size uniformity, less agglomeration, good oxidation resistance and low resistivity.
[0084] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing silver-coated copper powder, characterized in that: The following steps are involved: The first silver ammonia solution and the first reducing agent solution are simultaneously added dropwise to the deoiled and activated spherical copper powder dispersion, reacted for 5-20 minutes after the addition is completed, and then the second silver ammonia solution and the second reducing agent solution are simultaneously added dropwise, reacted for 25-40 minutes, filtered, washed with water, and dried to obtain the silver-coated copper powder; The concentration of the first silver ammonia solution is 0.3-2 mol / L; The concentration of the second silver ammonia solution is 0.005-0.1 mol / L.
2. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The activation solution used for the activation is selected from one of sulfuric acid solution, phosphoric acid solution, hydrochloric acid solution, benzenesulfonic acid solution, trifluoromethylbenzenesulfonic acid solution, C1-C4 alkylsulfonic acid solution and aminosulfonic acid solution.
3. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The average particle size of the spherical copper powder is 0.5-20 μm.
4. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The first reducing agent and the second reducing agent are independently selected from one or a combination of two or more of hydrazine hydrate, dimethylhydrazine, sodium borohydride, glucose, ascorbic acid and its salts, and tartaric acid and its salts.
5. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The molar ratio of the first silver ammonia in the first silver ammonia solution to the first reducing agent in the first reducing agent solution is 1:1-5.
6. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The molar ratio of the second silver ammonia in the second silver ammonia solution to the second reducing agent in the second reducing agent solution is 1:1-10.
7. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The molar concentration of the first silver ammonia solution is 20 times or more than the molar concentration of the second silver ammonia solution.
8. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The molar number of silver ammonia in the first silver ammonia solution is 30 times or more than the molar number of silver ammonia in the second silver ammonia solution.
9. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The end point of the water washing is that the conductivity of the washing liquid is less than 15 μs / cm.
10. A silver-coated copper powder, characterized in that: The silver-coated copper powder is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Silver-coated copper powder, preparation method thereof and electronic paste
CN111304640A
Cited By
High-density superfine silver-coated copper composite material and preparation method thereof
CN121696391A